Joint action: the ethical reason for Corporate Social Responsibility (Cultura Económica, 2019)
Is enlightened self-interest a reason to opt for a policy of corporate social responsibility? Is it enough as a moral reason or is it only a strategic reason? The author revises the recent debate prompted by the reports of The Economist about Corporate Social Responsibilityand looks for a more suitable reason based on the “social function of the corporation”. Preziosa understands the corporation as a result of collective action and as an institutional agent with moral character.
Keywords: corporate moral agency; moral status of corporations; corporate social responsibility; social role of the business company; collective action